FINANCIAL PERFORMANCE ANALYSIS AND ALMANT SCORE IN PT. PRIMA KARYA MANUNGGAL - Mahputera Mahputera (Jurnal Ilmu Manajemen Profitability, 2021)
The company's financial performance can be assessed through the company's financial statements presented. predicting the bankruptcy of a company needs to be analyzed using the Altman Method (Z-Score). as for the research objectives with this research we can find out the financial performance of PT. Prima Karya Manunggal from the last 3 years. The research method uses data collection techniques for the financial statements of PT Prima Karya Manunggal for the last 3 years and data analysis techniques using ratio analysis and Almant bankruptcy analysis. From the results of research and discussion, it can be concluded that the financial performance of PT. Prima Karya Manunggal from 2018 - 2020 based on the results of financial ratios, namely liquidity, solvency, profitability, and activity, it can be described that every year there is an increase and decrease and the Altman Z-Score method can be concluded that the financial performance of PT. Prima Karya Manunggal is classified as BANKRUPT (Financial Difficulties).